The trade-offs and synergies between food provisioning and soil conservation services in Guangxi province under the context of the conversion of cropland to forest and grassland - Yangling Zhao; Yifeng Qin; Caihua Yang; Veselin Krustev; Rongyan Zhao; Shengquan Che (ARPHA Proceedings)
The farmland-to-grassland-and-forest conversion program in Guangxi Province has enhanced soil conservation while significantly impacting regional food supply, highlighting the complex trade-offs between ecological protection and agricultural production. This study analyzed the spatiotemporal patterns of land use change, food supply services, and soil conservation services in Guangxi Province from 1990 to 2020, combined with Pearson correlation analysis, to reveal the dynamic relationship between the two. The results show that the farmland-to-grassland-and-forest conversion program has significantly altered the land use pattern in Guangxi Province, with arable land first increasing and then decreasing, while forest land has continued to increase. During this process, food supply services have shown an overall upward trend but with uneven spatial distribution; soil conservation services have declined, especially in the western and northern regions. The Pearson correlation coefficients between food supply services and soil conservation services in 2000, 2010, and 2020 indicate a significant negative correlation between the two, although this trade-off has eased by 2020. While the farmland-to-grassland-and-forest conversion program has improved the ecological environment, it has also had some impact on food production. However, with the advancement of ecological protection measures, the conflict between the two is gradually being mitigated. It is necessary to optimize land use practices to balance food production and ecological protection and achieve sustainable regional development.